ANALISIS POLA RETAK PADA STRUKTUR BALOK BETON BERTULANG DENGAN PERBANDINGAN BENTANG GESER - Elfania Bastian (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Reinforced concrete beams are one of the structural elements that have an important role in determining the quality of a structure. In the use of reinforced concrete the majority bear bending loads. For this reason, the selection of a reinforced concrete beam design must be calculated efficiently, including the possibility of concrete failure and cracking. In this study the authors conducted an analysis of reinforced concrete beams to determine crack patterns. To obtain the desired results, numerical modeling is carried out with three beams with different shear span comparisons to produce different capacities, namely beam 1 (a / d 1,869) having a load capacity of 234.60 kN, beam 2 (a / d 3,089) of 160.50 kN and beam 3 (4,878) of 102.10 kN. From the results of the analysis using ATENA software data obtained from the crack patterns of each beam. if 2.5 cracks a / d diagonally occur in the sliding region. And conversely 2.5